Microbiological screening tests for SARS-CoV-2 in the first hour since the hospital admission: A reliable tool for enhancing the safety of pediatric care - Vetrugno, Giuseppe; Grassi, Simone; Clemente, Francesco; Cazzato, Francesca; Rossi, Vittoria; Grassi, Vincenzo M.; Buonsenso, Danilo; Filograna, Laura; Sanguinetti, Maurizio; Focardi, Martina; Valentini, Piero; Ozonoff, Al; et al. (Frontiers in Pediatrics, 2022)
Introduction/purpose Since a significant proportion of SARS-CoV-2 infections occur within healthcare facilities, a multidisciplinary approach is required for careful and timely assessment of the risk of infection in asymptomatic patients or those whose COVID-19 diagnosis has not yet been made. The aim of this study was to investigate whether an adaptative model based on microbiological testing can represent a valid risk management strategy. Material and methods We collected data from the risk management unit database of a 1,550-bed tertiary hospital (Fondazione Policlinico Gemelli IRCCS, Rome, Italy) concerning pediatric admissions to the Emergency Department (ED) from 1 March 2020 to 31 December 2021. The study period was subdivided in period A and period B according to the technique used for the microbiological screening, respectively reverse-transcription polymerase chain reaction (RT-PCR) and antigen-detection test. Results In Period A, 426 children (mean age: 6 years) underwent microbiological screening at the ED. The total number of molecular tests performed was 463. 459/463 tested negative at the molecular test. In Period B, 887 children (mean age: 6 years) underwent microbiological screening in the ED. The total number of molecular tests performed was 1,154. 1,117/1,154 tested negative at the molecular test. Neither in Period A nor in Period B hospital-acquired SARS-CoV-2 infections were reported. Discussion and conclusion Despite high volumes, no cases of hospital-acquired SARS-CoV-2 infection have been reported. SARS-CoV-2 antigen-based tests can be used as a first-line option as they provide rapid results compared to RT-PCR, reducing the risk of infection in ED waiting rooms.